Toward an integrated pantropical ocean observing system - Gregory R. Foltz; Yassir A. Eddebbar; Janet Sprintall; Antonietta Capotondi; Sophie Cravatte; Peter Brandt; Adrienne J. Sutton; Tamaryn Morris; Juliet Hermes; Clive R. McMahon; Michael J. McPhaden; Lev B. Looney; et al. (Frontiers in Marine Science, 2025)
Global climate is regulated by the ocean, which stores, releases, and transports large amounts of mass, heat, carbon, and oxygen. Understanding, monitoring, and predicting the exchanges of these quantities across the ocean’s surface, their interactions with the atmosphere, and their horizontal and vertical pathways through the global oceans, are key for advancing fundamental knowledge and improving forecasts and longer-term projections of climate, weather, and ocean ecosystems. The existing global observing system provides immense value for science and society in this regard by supplying the data essential for these advancements. The tropical ocean observing system in particular has been developed over decades, motivated in large part by the far-reaching and complex global impacts of tropical climate variability and change. However, changes in observing needs and priorities, new challenges associated with climate change, and advances in observing technologies demand periodic evaluations to ensure that stakeholders’ needs are met. Previous reviews and assessments of the tropical observing system have focused separately on individual basins and their associated observing needs. Here we provide a broader perspective covering the tropical observing system as a whole. Common gaps, needs, and recommendations are identified, and interbasin differences driven by socioeconomic disparities are discussed, building on the concept of an integrated pantropical observing system. Finally, recommendations for improved observations of tropical basin interactions, through oceanic and atmospheric pathways, are presented, emphasizing the benefits that can be achieved through closer interbasin coordination and international partnerships.

Correction: Maritime Continent salinity as a new predictor for south Asian summer monsoon rainfall - Fuan Xiao; Mathew Koll Roxy; Dongxiao Wang (Climate Dynamics, 2025)

Maritime Continent salinity as a new predictor for South Asian summer monsoon rainfall - Fuan Xiao; Mathew Koll Roxy; Dongxiao Wang (Climate Dynamics, 2024)

Rapid climate change alters the environment and biological production of the Indian Ocean - Padmini Dalpadado; Mathew Koll Roxy; Kevin R. Arrigo; Gert L. van Dijken; Melissa Chierici; Marek Ostrowski; Rasmus Skern-Mauritzen; Gunnstein Bakke; Anthony J. Richardson; Erik Sperfeld (Science of The Total Environment, 2024)

Projected future changes in the contribution of Indo-Pacific sea surface height variability to the Indonesian throughflow - Vivek Shilimkar; Hiroto Abe; Mathew Koll Roxy; Youichi Tanimoto (Journal of Oceanography, 2022)
The Indonesian throughflow (ITF) transports a significant amount of warm freshwater from the Pacific to the Indian Ocean, making it critical to the global climate system. This study examines decadal ITF variations using ocean reanalysis data as well as climate model simulations from the Coupled Model Inter-comparison Project Phase 5 (CMIP5). While the observed annual cycle of ITF transport is known to be correlated with the annual cycle of sea surface height (SSH) difference between the Pacific and Indian Oceans, ocean reanalysis data (1959–2015) show that the Pacific Ocean SSH variability controls more than 85% of ITF variation on decadal timescales. In contrast, the Indian Ocean SSH variability contributes less than 15%. While those observed contributions are mostly reproduced in the CMIP5 historical simulations, an analysis of future climate projections shows a 25–30% increase in the Indian Ocean SSH variability to decadal ITF variations and a corresponding decrease in the Pacific contribution. These projected changes in the Indian Ocean SSH variability are associated with a 23% increase in the amplitudes of negative zonal wind stress anomalies over the equatorial Indian Ocean, along with a 12º eastward shift in the center of action in these anomalies. This combined effect of the increased amplitude and eastward shift in the zonal wind stress increases the SSHA variance over the Indian Ocean, increasing its contribution to the ITF variation. The decadal ITF changes discussed in this study will be crucial in understanding the future global climate variability, strongly coupled to Indo-Pacific interactions.

Tropical cyclones over the Arabian Sea during the monsoon onset phase - Shreyas Dhavale; Milind Mujumdar; Mathew Koll Roxy; Vineet Kumar Singh (International Journal of Climatology, 2022)
Generally, monsoon conditions are unfavourable for cyclogenesis in the Arabian Sea due to the strong vertical wind shear present over the basin which prevents the vertical development of cyclones. However, there are instances where tropical cyclones form over the basin during the onset phase of the Indian summer monsoon (ISM). The current study examines the evolution of the synoptic conditions in the years during 1979–2019 in which a cyclone forms during the onset phase of the ISM. The effect of various atmospheric and oceanic factors, the modulation of wind circulation over the Indian subcontinent and the north Indian Ocean region due to the possible influence of tropical and extratropical weather systems has been taken into consideration. Our analysis indicates that a weak mean monsoonal wind circulation caused by the southward intrusion of subtropical westerlies (at 200 hPa) is conducive for cyclogenesis over the Arabian Sea during the monsoon onset phase. Such a weak onset phase of the monsoon, coupled with the seasonal warm SSTs, may lead to cyclone formation in the Arabian Sea.

Simulation of interannual relationship between the Atlantic zonal mode and Indian summer monsoon in CFSv2 - Vijay Pottapinjara; Mathew Koll Roxy; M. S. Girishkumar; Karumuri Ashok; Sudheer Joseph; M. Ravichandran; R. Murtugudde (Climate Dynamics, 2021)

Ocean Climate Observing Requirements in Support of Climate Research and Climate Information - Detlef Stammer; Annalisa Bracco; Krishna AchutaRao; Lisa Beal; Nathaniel L. Bindoff; Pascale Braconnot; Wenju Cai; Dake Chen; Matthew Collins; Gokhan Danabasoglu; Boris Dewitte; Riccardo Farneti; et al. (Frontiers in Marine Science, 2019)

Indian Ocean and Indian summer monsoon: relationships without ENSO in ocean–atmosphere coupled simulations - Julien Crétat; Pascal Terray; Sébastien Masson; K. P. Sooraj; Mathew Koll Roxy (Climate Dynamics, 2017)

Impacts of Indian and Atlantic oceans on ENSO in a comprehensive modeling framework - Pascal Terray; Sébastien Masson; Chloé Prodhomme; Mathew Koll Roxy; K. P. Sooraj (Climate Dynamics, 2016)

Sensitivity of precipitation to sea surface temperature over the tropical summer monsoon region—and its quantification - Mathew Roxy (Climate Dynamics, 2014)

Intraseasonal SST-precipitation relationship and its spatial variability over the tropical summer monsoon region - Mathew Roxy; Youichi Tanimoto; B. Preethi; Pascal Terray; R. Krishnan (Climate Dynamics, 2013)

Influence of sea surface temperature on the intraseasonal variability of the South China Sea summer monsoon - Mathew Roxy; Youichi Tanimoto (Climate Dynamics, 2012)

Seasonality in the relationship between El Nino and Indian Ocean dipole - Mathew Roxy; Silvio Gualdi; Hae-Kyung Lee Drbohlav; Antonio Navarra (Climate Dynamics, 2011)